Public Relations ..... Dialectic of concept and practice A critical study of the levels of persuasion and influenc - bourahla, slimen (Journal of Social Sciences and Humanities, 2025)
This study aimed to highlight some levels of influence in public relations and discuss its outputs (influence) that appear clearly when comparing the theoretical aspects of theoretical concepts with actual practices, as public relations departments in any institution seek to achieve interaction with its audience, whether internally or externally, trying to persuade and influence it through responsible and social acceptable performances, but the observer and contemplator of the real and actual practice of its activities at the present time finds the multiplicity of levels of its impact on the public, which may sometimes reach the point of misleading, deception and manipulation, and these methods which essentially intervene in the propaganda operations,.the study found that public relations are not always positive in their interaction with the public, but hide some negative aspects that appear in some influential levels represented mainly in: negative influence, and persuasion misleading, engineering of consent and approval, and this is evident during the management of conflicts, crises and wars by practitioners of public relations for the institutions and organizations they represent.